What is the stimulus for the excavation of fungus chamber in leaf-cutting ants? - Camargo, Roberto da Silva [UNESP]; Forti, Luiz Carlos [UNESP] (Springer, 2015)
This study investigated the stimulus for the excavation of fungus chamber by leaf-cutting ants (Atta sexdens rubropilosa) during nest building. Thus, it was hypothesized that the fungus garden or the brood is a stimulus for excavating the chamber. Therefore, four treatments were designed: treatment 1, fixed number of workers (30), without the fungus garden and brood; treatment 2, fixed number of workers (30), with fungus garden (average weight 1.5 g) and without brood; treatment 3, fixed number of workers (30), without the fungus garden and with brood (30 larvae or pupae); and treatment 4, fixed number of workers (30), with fungus garden (average weight 1.5 g) and brood items (30 larvae or pupae). The variables studied were (a) morphological structure parameters (size and thickness of tunnels and the chamber formed (in centimeters)), (b) workers'excavation flow, and (c) soil volume excavated every 24 h. As expected, the results support the hypothesis that the fungus garden and brood are a stimulus for excavating the chamber. The hypothesis is confirmed by the absence of a functional structure, such as a chamber, when the symbiotic fungus and brood are absent. We can then conclude that the presence of the fungus garden and brood stimulate the workers to a greater excavation activity, resulting in functional structures such as tunnels and chamber.
Keywords: Atta sexdens rubropilosa; Digging behavior; Leaf-cutting ants; Nest excavation